Characterization of Mycobacterium chelonae-Like Strains by Comparative Genomics - Nogueira, Christiane L.; de Almeida, Luiz G. P.; Menendez, Maria C.; Garcia, Maria J.; Digiampietri, Luciano A.; Chimara, Erica; Cnockaert, Margo; Palomino, Juan C.; Portaels, Françoise; Martin, Anandi; Vandamme, Peter; Leão, Sylvia C. (Frontiers in Microbiology, 2017)
Isolates of the Mycobacterium chelonae-M. abscessus complex are subdivided into four clusters (CHI to CHIV) in the INNO-LiPA® Mycobacterium spp DNA strip assay. A considerable phenotypic variability was observed among isolates of the CHII cluster. In this study, we examined the diversity of 26 CHII cluster isolates by phenotypic analysis, drug susceptibility testing, whole genome sequencing and single-gene analysis. Pairwise genome comparisons were performed using several approaches, including average nucleotide identity (ANI) and genome-to-genome distance (GGD) among others. Based on ANI and GGD the isolates were identified as M. chelonae (14 isolates), M. franklinii (2 isolates) and M. salmoniphium (1 isolate). The remaining 9 isolates were subdivided into three novel putative genomospecies. Phenotypic analyses including drug susceptibility testing, as well as whole genome comparison by TETRA and delta differences, were not helpful in separating the groups revealed by ANI and GGD. The analysis of standard four conserved genomic regions showed that rpoB alone and the concatenated sequences clearly distinguished the taxonomic groups delimited by whole genome analyses. In conclusion, the CHII INNO-LiPa is not a homogeneous cluster; on the contrary, it is composed of closely related different species belonging to the M. chelonae-M. abscessus complex and also several unidentified isolates. The detection of these isolates, putatively novel species, indicates a wider inner variability than the presently known in this complex.